Reproductive Costs for Hybridizing Female Anasa tristis (Hemiptera: Coreidae), but No Evidence of Selection Against Interspecific Mating. Issue 4 (27th August 2018) - Hamel, Jennifer A; Eskeland, Emma E; Lehmann, Tyler K; Stover, Paige L
Abstract: Individuals of different species sometimes mate in nature, and such behavior often carries costs, such as wasted gametes and inviable offspring. One context in which interspecific mating commonly occurs is when closely related species come into secondary contact. Here, we tested whether reproductive isolation is greater in an area of recent secondary contact than in allopatry for two closely related insect species, and we examined whether mating between individuals of these two species constitutes reproductive interference. In Florida, two species of squash bugs (Hemiptera: Coreidae: Anasa tristis DeGeer and Anasa andresii Guérin-Méneville) have been secondarily sympatric for ≥80 generations, and male A. andresii copulate with female A. tristis . Because hybridization is often costly for females, we predicted that secondarily sympatric females would be less likely to mate with heterospecifics than would allopatric females. We found no evidence of recent selection on reproductive isolation: females from both populations were equally likely to mate with heterospecifics, and heterospecific males did not make more mating attempts than conspecifics to achieve copulations. However, female A. tristis paired with heterospecifics produced many fewer eggs and offspring than females paired with conspecifics, and this did not differ according to whether females were from allopatric or sympatric populations. Our findings show that reproductive barriers between these species existed before secondary contact. We suggest that habitat use may limit encounter frequency, and that female choice, multiple mating, and postcopulatory processes may reduce costs for females. Consequently, we suggest that mating systems and ecological factors mediate the effects of reproductive interference.